There's More to Life Than Money: Exploring the Levels/Growth Paradox in Income and Health - Kenny, Charles (2012)
This paper discusses historical and recent cross-country evidence relating income to measures of health. After a review of the literature on income and the quality of life, the paper looks at long-term historical evidence on the link between income change and health indicators. Using data on life expectancy, infant mortality and income for a small subset of largely wealthy countries over the 1913-1999 period, the paper examines correlations between income and health at period start and end as well as using the growth of the variables. Using a larger set of data over the period 1975-2000, the paper repeats these tests, as well as looking for any evidence of a larger impact of income, when different data are used or the sample is split. Results suggest a strong cross-country link between income and health and considerable evidence of global improvements over time, but a comparatively weak relationship between improvements in income and improvements in health, even over the very long term. The paper discusses a model based on technology and institutions that might account for such results as well as some preliminary evidence in favour of such a model.